GOOGLE TRANSLATE AND ITS ROLE IN ACADEMIC WRITING FOR UNIVERSITY STUDENTS - Fibriana, Intan; Ardini, Sukma Nur; Affini, Laily Nur (Study Program of English Literature, 2021)
This study aims to determine Google Translate as a translation machine, used in academic writing for university students in the English Education Department. The objectives of this study are to (1) find out the use of Google Translate for the students in academic writing, (2) find out the advantages and disadvantages of using Google Translate in academic writing, and (3) find out the students' perspectives of Google Translate to their study towards the subject. This study occupied a descriptive qualitative method, and the instrument was a questionnaire. This study's participants were the students in the fifth-semester of Universitas PGRI Semarang who studied in 2020. The findings showed that students used Google Translate for translating words, new vocabulary, sentences, paragraphs, texts, and compose their sentences. There are both advantages and disadvantages of using Google Translate in academic writing. Google Translate benefited them in correcting the words' spelling, translating words, knowing the general meaning of texts, and finding the vocabulary they never knew before. The disadvantages were that sometimes: it served incorrect grammar, the translation was inaccurate, the meaning did not fit the context, the structure of the sentences was unarranged correctly, and some words were hard to understand. From the students' perspective, most students agreed that using Google Translate in academic writing was not considered cheating. They admitted that using Google Translate was useful and helpful for their study in academic writing. The students thought that the inaccurate result of Google Translate result was unable to improve the students' academic writing competence.